Effect of organic matter, simple superphosphate and potassium chloride on the percentage of the macronutrients of the dry matter of the aerial part of the yellow passion fruit. - Peixoto, José Ricardo (Pesquisa Agropecuaria Brasileira, 2014)
- A study was carried out to verify the effect of organic in matter, simple superphosphate and potassium chioride on the percentage of macronutrients ia the dry matter of the aerial part of the yellow passion fruit (Pass(flora edulis f. flavicarpa Deneger). The experiment was carried out in a seedling nursery of ESAL - Lavras, MG, Brazil, from September to November 1984. The experimental design, used was completely randomized in a 4 x 4 x 3 factorial scheme, the factors being 4 dosages of organic matter, 4 dosages of simple superphosphate and three dosages of potassium chloride with three replicates, in a total of 48 treatments and 144 plots, each plot comprising six polyethylene bags. The seedlings were removed 70 days after sowing in order to carry out the evaluations. The increase in the dosages of organic matter caused and increase in the values of the percentage of Mg in the dry matter of the aerial part. The increase in the dosages of simple superphosphate caused an increase in the values of the percentage of Ca and decrease of N, K and Mg in the dry matter of the leaf area. The increase in the dosages of potassium chloride caused an increase in the values of percentage of K and decrease of N and Mg in the dry matter of the leaf area.